Time course of organ and hematological response to complement blockage in transplant-associated thrombotic microangiopathy after allogeneic hematopoietic stem cell transplantation - Rudakova, Tatiana A.; Vlasova, Julia Yu; Paina, Olesya V.; Slesarchuk, Olga A.; Gorodnova, Marina A.; Schegoleva, Tatiana S.; Goloshchapov, Oleg V.; Bykova, Tatiana A.; Morozova, Elena V.; Zubarovskaya, Lyudmila S.; Moiseev, Ivan S.; Kulagin, Alexander D. (Frontiers in Medicine, 2025)
BackgroundHematopoietic stem cell transplantation (HSCT) offers a potential cure for various hematologic malignancies and non-malignant disorders but is often accompanied by severe complications, one of the most challenging being transplant-associated thrombotic microangiopathy (TA-TMA). Eculizumab, a complement inhibitor, has emerged as an effective therapeutic option for TA-TMA.MethodsThis single-center retrospective study was conducted at Pavlov University, St. Petersburg, to evaluate the efficacy of eculizumab in 14 adult and pediatric patients who developed high-risk TA-TMA following HSCT between 2015 and 2023. Treatment response was assessed by monitoring organ functions, blood counts, transfusion requirements, the presence of schistocytes in peripheral blood, and increased serum lactate dehydrogenase (LDH). The primary endpoint was overall survival at 100 days from eculizumab administration. Secondary endpoints included the cumulative incidence of a 25% decrease in serum lactate dehydrogenase levels and to the limit of the normal range for age from the date of the initiation of eculizumab, the cumulative incidence of a 50% increase in platelet count or stable platelet levels ≥ 20×109/l was 74% (95% CI, 32–92) with median time 21 days (range: 1–104), cumulative incidence of platelet level ≥ 50×109/l, and 1 year from the date of the initiation of eculizumab.ResultsOverall survival at 100 days was 57% (95%CI, 36–90). The cumulative incidence of LDH decreased by 25% was 89% (95% CI, 26–99) with a median time of 11 days (range: 2–27). Cumulative incidence of LDH ≤ 1.5 upper reference limits (URLs) after eculizumab therapy was 73% (95% CI, 34–91) with a median time of 22 days (range: 2–170). The cumulative incidence of a 50% increase in platelet level or stable platelet level ≥ 20×109/l was 74% (95% CI, 32–92) with a median time of 21 days (range: 1–104). The cumulative incidence of platelet level ≥ 50×109/l was 56% (95% CI, 22–80) with a median time of platelet increase of 75 days (range: 5–384). Complete response was documented in 57% of the group.DiscussionIn summary, eculizumab is a well-tolerated promising therapeutic intervention for TA-TMA, but more studies are needed to establish its timing and dosage regimen in TA-TMA.